Comparison of Î²-Glucanases Production by Acremonium sp. IMI 383068 in Batch and Continuous Culture System - Jayus, Jayus (UNEJ e-Proceeding, 2014)
Studies on the possible influence of physical environmental factors on extracellular b-glucanase production by Acremonium sp. IMI 383068 were undertaken, in particular to assess the role of varying agitation speed and pO2 levels, since these have been shown in other studiesto affect the yields of other fungal extracellular enzymes. The use of chemostat cultures in this present study meant that the possible influence of these two parameters on enzyme production could be controlled independently of each other and of growth rate. No other similar data on possible factors affecting fungal (1->3)- and (1->6)-b-glucanases are available in the literature, and therefore other fungal extracellular enzyme systems are used here as comparisons for this discussion. To investigate the possible relationship between enzyme production and culture morphology, the HGU values or branching frequencies of the fungal hyphae were assessed. Since substantial conidial production also occurred in these cultures of Acremonium sp. IMI 383068, it was not possible always to distinguish between mycelial branches that were true vegetative hyphae and those eventually forming the short tapered lateral conidiophores that characterize this strain. Hence HGU determinations include both of these two branch types, except where it was obvious that the branch in question was a conidiophore, adjudged by the presence of emerging conidia from it. The major findings of this study will be discused here which were mainly engaged to the relationship between production of (1->3)-b-glucanases and the growth of the fungus, where it was growth rate dependent, while that of the (1->6)-b-glucanase was growth rate independent. The production ofÂ (1->3)-b-glucanases was shear sensitive and also depended on O2 availability in the culture medium. Based on the data from both batch and chemostat culture, it was found that there was no clear relationship between branching frequency of the fungal mycelium and b-glucanase production by the fungus.Keywords: b-glucanases, Acremonium, HGU, batch and chemostat, branching frequency